Journalism research and investigation in a digital world - Tanner, Stephen; Richardson, Nick (South Melbourne, Vic. : Oxford University Press, 2013)
From wearing out shoe leather to the latest technologies, Journalism Research and Investigation in a Digital World helps journalism students and journalists who are embarking on their careers learn how to conduct complex investigations. It recognises that journalists need to develop skills that will enable them to work across a range of media platforms, while adapting to the new technology that will help them locate, interpret and package information in a faster, more efficient way. Key features: Practical case studies written by a range of journalists in the field documenting how they tackled a particular story. Highlights international and local examples, including Wikileaks and investigative social journalism and the Arab Spring. Written to allow readers to pick and choose the chapters and case studies to suit their immediate needs. Journalism Research and Investigation in a Digital World is also available as an e-book.
Includes bibliographical references and index.
Keywords: Journalism -- Research; Digital media; Online journalism